Towards development of software testing competency framework to empower software testers' profession - Idrus H.M.; Ali N. (Science Publishing Corporation Inc, 2023)
Separation of job functions between developers and testers due to enforcement of Software Quality Assurance (SQA) concept in software development has created worldwide demands for highly skillful software testers. This job function separation is to ensure that the systems or applications being developed are transparent at its testing activities. This will eventually lead to better quality of software products that will minimize impact or issues regarding software or system errors, bugs or faults. The aim of this article is to discuss on the current nature of software testing industry for identification of competencies issues or challenges related to software testers. This paper is intended to propose a software testing competency development framework as a job profiling, competencies assessment, training needs and professional career development for software testers. It is targeted that the proposed competency development framework will benefit software tester as individual, public or private agencies as organizations and education institutions as academia. 2018 Authors.